Effect of Spinach Extract Supplementation Combined with Iron Tablets on Hemoglobin Concentration among Pregnant Women: A Quasi-Experimental Study - Hernawati, Yeti; Korihah, Haerani; Setiawan, Deris Riandi (Journal of Applied Nursing and Health, 2026)
Background: Anemia during pregnancy remains a significant maternal health problem, primarily associated with reduced hemoglobin concentration. Although iron tablet supplementation is a standard intervention in antenatal care, its effectiveness may be enhanced through complementary nutritional strategies. However, limited evidence exists regarding the effectiveness of spinach extract supplementation combined with iron tablets as an adjunct to routine iron supplementation among pregnant women. Therefore, this study aimed to evaluate the effect of spinach extract supplementation on hemoglobin concentration in pregnant women. Methods: This quasi-experimental pretest–posttest two-group study with a control group was reported in accordance with the Transparent Reporting of Evaluations with Nonrandomized Designs (TREND) guideline. A total of 60 pregnant women were selected using purposive sampling and allocated to either the intervention or control group through nonrandom assignment based on existing antenatal care groupings. The intervention group received spinach extract supplementation combined with iron tablets combined with iron tablets, while the control group received iron tablets only for 14 days. Hemoglobin concentration was measured at baseline and after the intervention using an EasyTouch GCHb hemoglobin meter. Data were analyzed using paired-samples t-tests and independent-samples t-tests. Results: Hemoglobin concentration increased significantly in both groups after the intervention. At baseline, there was no significant difference in mean hemoglobin concentration between the intervention and control groups. After the intervention, the intervention group had a significantly higher mean hemoglobin concentration than the control group. The mean hemoglobin change was 1.12 ± 0.32 g/dL in the intervention group and 0.76 ± 0.33 g/dL in the control group. The between-group difference in hemoglobin change was 0.36 g/dL (95% CI: 0.19–0.53; p < 0.001), with a large effect size (Cohen’s d = 1.11). Conclusion: Spinach extract supplementation combined with iron tablets may provide an effective complementary strategy for improving hemoglobin concentration among pregnant women. However, further randomized studies with larger sample sizes and longer follow-up periods are recommended to confirm these findings.